2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16650
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Peer Led Team Learning In Gateway Science And Mathematics Courses For Engineering Majors

Abstract: The large lecture format found in most introductory mathematics and science courses is generally not conducive to a teaching-learning process that would allow for the development of professional skills such as team work, oral and written communication, and time management. Motivated by a successful experience in a general chemistry course, we have implemented workshops based on the Peer Led Team Learning (PLTL) model that engages every engineering student enrolled in the introductory chemistry, mathematics, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…PLTL student success measures were evaluated in a variety of undergraduate disciplines, including: general chemistry; ,,− organic chemistry; allied health, which is also called GOB; introductory biology; , anatomy and physiology; bioinformatics; mathematics; computer science; , engineering; psychology; and physics . Although implementation of PLTL has been reported in a high school setting, no peer-reviewed articles were available at the time of this review article.…”
Section: Student Success Measures As a Means Of Program Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…PLTL student success measures were evaluated in a variety of undergraduate disciplines, including: general chemistry; ,,− organic chemistry; allied health, which is also called GOB; introductory biology; , anatomy and physiology; bioinformatics; mathematics; computer science; , engineering; psychology; and physics . Although implementation of PLTL has been reported in a high school setting, no peer-reviewed articles were available at the time of this review article.…”
Section: Student Success Measures As a Means Of Program Evaluationmentioning
confidence: 99%
“…Gafney and Varma-Nelson stated that nearly 90% of the participants in their study who had earned their undergraduate degree were enrolled in medical or graduate school, employed in a science field, or engaged in teaching. Likewise, Flores et al reported that the six-year graduation rate for peer leaders of gateway math and science courses for engineers was 48% higher than the overall undergraduate graduation rate (97% vs 49%). However, the comparison of graduation rates of peer leaders and nonpeer leaders with similar academic backgrounds would be more compelling, since peer leaders tend to be excellent students.…”
Section: Research On Peer Leadersmentioning
confidence: 99%
“…An additional benefit of PLTL is the benefit to the peer leaders themselves. Several studies have reported higher grades for peer leaders ( 8 10 ), higher graduation rates ( 11 ), motivated peer leaders declaring a major in the subject ( 8 ) or taking more courses ( 9 ) in that discipline, access to new methods of learning ( 12 ), acquiring facilitation and leadership skills ( 13 15 ), and an appreciation and growing interest in being a teacher ( 8 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%